Kajian Arsitektur Bioklimatik pada One East Surabaya - Ahnaf Wiryawan, Evan; Arfianti, Ami (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
At this time the population is increasing, along with this the needs of society are also increasing. The community is starting to carry out various kinds of development to meet these needs, one of which is in the residential sector, namely apartments. Apartments are the choice of urban communities as a place to live because of their strategic location and offering various facilities. As a place to live, apartments need to prioritize comfort in order to improve the quality of life of their users. Bioclimatic architecture is a concept for creating a building that responds to the surrounding climate so that there is a balance between humans and the environment. The design principle of bioclimatic architecture is to prioritize climate adjustment to achieve energy efficiency and thermal comfort. This research examines the concept of bioclimatic architecture by taking the One East Surabaya Apartment as an object. This research uses a qualitative descriptive method with secondary data collection through sources in the form of literature studies. The aim of this research is to identify and provide insight regarding the application of the concept of bioclimatic architecture based on aspects of the principles of bioclimatic architecture in apartment buildings. From the results of this research, it was found that the One East Surabaya Apartment has met bioclimatic building standards obtained from the transition space/balcony, relationship to the landscape, design on the walls and the use of passive shading tools.